Human Platelet Factor 4 and Its C-Terminal Peptides: Heparin Binding and Clearance from the Circulation - Rucinski, Boguslaw; Niewiarowski, Stefan; Strzyzewski, Marian; Holt, John C; Mayo, Kevin H (Thrombosis and Haemostasis, 1990)
Human platelet factor 4 (PF4), a high affinity heparin binding protein, is released from stimulated platelets and stored at vascular sites, predominantly in liver, from where it can be brought back into circulation by heparin. We attempted to define structural requirements for PF4 binding to heparin and for the pattern of its clearance from the circulation. Intact PF4 bound strongly to heparin agarose and was eluted at 1.4 M NaCl, while reduced PF4 and PF4 C-terminal peptides PF4 (47-70) and PF4 (58-70) bound weakly and were eluted at 0.2-0.5 M NaCl. 125I-radiolabeled intact PF4, reduced PF4 and C-terminal PF4 peptides injected into rabbits were cleared from the circulation in a biphasic pattern with components having half-life time of 1-2 min and 20-140 min. Heparin eliminated the fast component of PF4 clearance, but it did not affect clearance of reduced PF4 or C-terminal PF4 peptides. In contrast to reduced PF4 and PF4 (47-70), intact PF4 that accumulated in the liver and spleen, was displaced by heparin into circulating blood. In conclusion, specific binding sites and native conformation of the molecule are critical for high affinity PF4 binding to insolubilized heparin and for a pattern of PF4 clearance from the circulation in the presence of heparin.